Production and Characterization of Alumina-Titania Biocomposite - ÇETİNER, BURCU NİLGÜN; ERKMEN, ZİYA ENGİN (AMER INST PHYSICS, 2015)
Alumina is a biomaterial of choice for more than 20 years due to its high hardness accompanied by low friction, wear and inertness to in vivo environment. It has been reported that titanium oxidized to the rutile phase is bioactive. This is a property discovered for certain ceramics such as Bioglass and sintered hydroxylapatite (HA). But the combination of alumina and titania forming tialite (Aluminium titanate-50 mol % Al2O3 and 50 mol % TiO2) is a new challenge. In this work we made firstly the beneficiation of the Seydisehir alumina by leaching it in the acidic solution the Aqua Regia followed by preparation of batches containing 2,5 wt %, 3,5 wt % and 4,5 wt % of MgO as the sintering aid, 1 wt % of SiO2 and the balance; the alumina and titania powder mixture (1:1 mole). After sintering these batches at 1600 degrees C for about 12 h, their mechanical properties (the compression and hardness testings) and phase ratios (the XRD analysis) were analyzed and compared with the control group containing the laboratory scale alumina instead of the Seydisehir alumina. Following the characterization (the SEM and the EDS analysis) of the substrate material, the comparison of two different materials was carried out.
Keywords: Tialite; Seydisehir Alumina; bioceramic composites and structural properties; SOL-GEL SYNTHESIS; CERAMICS; COMPOSITES